Monster Hunters - Lorey, Dean.; Dorman, Brandon (New York : HarperCollins, 2008)
Rescued from a very sheltered life, thirteen-year-old Charlie learns that the monsters of his nightmares are real when he becomes a student at Nightmare Academy and begins training to harness his powers to fight terrible creatures and return them to the Netherworld.
Keywords: Monsters -- Juvenile fiction; Schools -- Juvenile fiction; Friendship -- Juvenile fiction; Nightmares -- Juvenile fiction; Fantasy fiction